The Influence of Motivation, Work Environment through Commitment towards Teacher Performance (Regional Office of Education Division of Kunduran Sub-district, Blora Regency) - Nurilla, Asma Azizah; Raharjo, Tri Joko; Sudana, I Made (Educational Management, 2019)
The aims of this study were to describe and analyze the partial and simultaneous influence of motivation and work environment as well as commitment towards teacher performance in organizing learning activity. This study also examined the influence of motivation and work environment through commitment on teacher performance in organizing learning activity. This study was a population study in which using quantitative method and survey approach. Data collection was done by using questionnaire distributed to 138 teachers. Data analysis used multiple linear regression analysis and path analysis. The results showed that motivation influenced on teacher commitment as big as 1.7%. Work environment had influence on teacher commitment as big as 47.9%. The influence of motivation and work environment on teacher commitment was 63.7%. While, motivation towards teacher performance was 14.7%. The influence of work environment on teacher performance was 9.3%. The influence of commitment towards teacher performance was equal to 12.6%. There was influence of motivation, work environment and commitment towards teacher performance which was equal to 59.1%. There was no influence of motivation on teacher performance through commitment because the value of Indirect Effect is smaller than the value of Direct Effect.